Troubled waters : confronting the water crisis in Australia's cities - Troy, Patrick N. (Patrick Nicol), 1936-2018 (ANU E Press, 2008)
"The traditional way water services have been provided has been to rely on predict and provide approaches that have given primacy to consideration of the supply of water services. This approach has been given a more economistic flavour in recent times. This book is designed to explore the nature of the demand for urban water services and how that has changed over the last century. It will discuss how the demand for centralised provision of urban water services might be re-shaped to enable urban areas to better cope with the water supplies that might be expected to change as the cities adjust to climate change."--Provided by publisher